IMPROVING STUDENTS’ LISTENING COMPREHENSION ON NARRATIVE TEXT BY CARTOON FILM “MY LIFE AS A TEENAGE ROBOT” - Ega Ayu Dwi Saputri; Eni Rosnija; Wardah Wardah (Universitas Tanjungpura, 2019)
AbstractThe aim of this research was to know how cartoon film “My Life as a Teenage Robot” improved students’ listening comprehension on narrative text. This research was conducted using Classroom Action Research in three cycles. The data were collected using field notes, teachers’ interview and students’ listening tests result. The participants were the English teacher and 20 students of X IIA class of SMAN 8 Singkawang in Academic Year 2018/2019. The result of this research showed that the listening activity using cartoon film “My Life as a Teenage Robot” improved students’ listening comprehension on narrative text from cycle 1 to cycle 3. First, the cartoon films attracted the students’ attention during the listening activity. Second, the students became more active to participate in discussion during the listening activity especially during the Introducing the Topic stage and Rewinding the Video stage. Third, the students were aware of their mistakes because of the correction from the teacher and the other students during the Rewinding the Video stage. Dividing the video into three parts helped the students to gather specific information and to answer the questions. Using pictures of the cartoon film during the Introducing the Topic stage trigged the students to brainstorm critically and creatively. Moreover, the mean score of students’ listening tests increased and met the standard score (70). Keywords: Listening Comprehension, Narrative Text, Cartoon Film, Classroom Action Research